Cross-linguistic evidence for gender as a prominence feature - Esaulova, Yulia; Von Stockhausen, Lisa (Frontiers in Psychology, 2015)
This paper discusses recent findings in the online sentence processing research that suggest to consider gender information a prominence feature. Prominence features are hierarchically ordered information types that interact with formal features of arguments (e.g., grammatical functions, thematic roles) and thus determine the readers’ ability to efficiently interpret linguistic ambiguities. While previous research addressed a number of prominence features (e.g., animacy, definiteness, person), there is now first empirical evidence indicating that gender information also influences the assignment of thematic roles across languages. Grammatically masculine role nouns are processed faster as agents than patients compared to feminine ones. Stereotypically male role nouns (e.g., electrician) are integrated with an agent role easier than neutral ones (e.g., musician), which in turn are integrated easier than female ones (e.g., beautician). Conceptualizing gender as a prominence feature will not only expand our knowledge about information types relevant for online comprehension but also uncover subtle gender biases present in language. The present work explores the possibility for a theoretical integration of social psychological and psycholinguistic research focusing on gender with research on prominence. Potential advantages an interdisciplinary approach to the study of gender as a prominence feature, open questions and future directions are discussed.